Other Organizations Parading With Arms, §§ 44-45, Ch. 163, Session Laws of the State of Wyoming (1925). - (:unkn) unknown (My University, 1925)
It shall not be lawful for any body of men whatso§ ever, other than the regularly organized National Guard or the troops of the United States, to associate themselves together as a military company or organization
Keywords: MILITIAS